2011
DOI: 10.1007/s10856-011-4327-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of fluorapatite cement for dental enamel defects repair

Abstract: In order to restore the badly carious lesion of human dental enamel, a crystalline paste of fluoride substituted apatite cement was synthesized by using the mixture of tetracalcium phosphate (TTCP), dicalcium phosphate anhydrous (DCPA) and ammonium fluoride. The apatite cement paste could be directly filled into the enamel defects (cavities) to repair damaged dental enamel. The results indicated that the hardened cement was fluorapatite [Ca(10)(PO(4))(6)F(2), FA] with calcium to phosphorus atom molar ratio (Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
3
23
0
1
Order By: Relevance
“…09-0432), 10 suggesting that the crystals were fluoridated HA. 15 The sharp and intense 002 peak indicated that the crystals were wellcrystallized and oriented along their c axis; these results are consistent with the observations in the SEM images ( Figure 5). After 6 days of incubation, the XRD pattern showed that the diffraction peaks around 2θ of 32°were split and clear, which implies good crystallinity of fluoridated HA.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…09-0432), 10 suggesting that the crystals were fluoridated HA. 15 The sharp and intense 002 peak indicated that the crystals were wellcrystallized and oriented along their c axis; these results are consistent with the observations in the SEM images ( Figure 5). After 6 days of incubation, the XRD pattern showed that the diffraction peaks around 2θ of 32°were split and clear, which implies good crystallinity of fluoridated HA.…”
Section: Resultssupporting
confidence: 89%
“…17 There was no −OH group-specific peaks at 1571 cm −1 , indicating that the −OH group might be replaced by an F group to form fluoridated HA. 15 It should be noted that some information might be lost because of the reflection mode of FTIR, which makes it difficult to distinguish between FA and HA. Thus, these data should be analyzed in conjunction with other methods, such as XRD and morphological change of the crystals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-setting FA-forming formulations are also known; they can be prepared by the same way but in the presence of soluble F − -ions [37,232,233] 1.3 ] as the end-product [69,234]. As both CDHA and carbonate apatite are formed in an aqueous environment and have a low crystallinity, they appear to be rather similar to the biological apatite of bones and teeth.…”
Section: Apatite-forming Formulationsmentioning
confidence: 99%
“…In vivo studies are showed that fluorapatite material had osteoconductive properties [19]. In vitro studies have showed that the cytotoxic, genotoxic and mutagenic effects of fluorapatite and fluorhydroxyapatite materials have no effect or are negligible [20][21][22]. Several studies are showed that FAP materials have antibacterial activities but not the biocidal effect [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%